2010
DOI: 10.1111/j.1524-4733.2010.00744.x
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-Effectiveness of Spinal Cord Stimulation for Complex Regional Pain Syndrome

Abstract: In selected patients with CRPS, SCS is cost-effective as an adjunct to CMM. Despite their initial increased expense, rechargeable IPGs should be considered when IPG longevity is likely to be short. These findings support policymakers to extend the use of SCS as a good value for money treatment for CRPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 21 publications
2
68
1
2
Order By: Relevance
“…11,22 CRPS is commonly associated with substantial disability, loss of quality of life and personal and societal economic burden. 26,27 …”
Section: Epidemiologymentioning
confidence: 99%
“…11,22 CRPS is commonly associated with substantial disability, loss of quality of life and personal and societal economic burden. 26,27 …”
Section: Epidemiologymentioning
confidence: 99%
“…In addition, it has an advantage over the implanted system for patients requiring higher amplitudes of stimulation. As a result, the rechargeable IPG is gaining popularity due to its small size and ease of maintenance [7,8]. …”
Section: The Technologymentioning
confidence: 99%
“…Mancia et al, 14 in a prospective, randomized, controlled, multicenter study, concluded that the patients with combined SCS and medical management were more costly to the healthcare system, but also had significant functional improvement. Kumar et al 15 16 concluded that ''in selected [complex regional pain syndrome] patients, SCS is a cost-effective option as an adjunct to conventional medical management.'' They also concluded that a rechargeable generator is the most cost-effective option, when the predicted generator longevity is >4 years, despite higher initial cost.…”
Section: Permanent Implantationmentioning
confidence: 99%